(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Cryptogenic organizing pneumonia is lately recognized distinctly rare clinico-pathological entity. It affects both sexes with equal predisposition in 5th-6th decade. Generalized symptomatology resembling viral fever complicates specific diagnosis. Autopsy diagnosis of it is even rare. This entity was diagnosed at post-mortem in a case of fatal accidental electrocution in an eight year old boy. Authors discuss this first reported cryptogenic organizing pneumonia in pediatric age, diagnosed at autopsy or otherwise along with review of literature and medico-legal implications in such accidental deaths. Fatal or non-fatal cryptogenic pneumonia has been un-reported before either at autopsy or otherwise in similar age and circumstances.